Adaptation of Mindfulness in Parenting Questionnaire (MIPQ) for parents of children aged 2-12 years - Febriani, Zulfa; Setyowati, Retno Budi; Kumalasari, Dewi; Fourianalistyawati, Endang (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Mindful parenting intervention programs and characteristics can support positive parenting conditions and have an impact on children's psychosocial development. However, the measurement of mindful parenting has not been widely developed, although one example is the Mindfulness in Parenting Questionnaire (MIPQ) scale, which has good psychological properties and has been validated in several countries. This study aims to obtain evidence of the validity of the interpretation of the Indonesian version of the MIPQ scale (MIPQ-Ind) amongst a population of parents with children aged 2 -12. The participants were 822 parents (268 fathers and 554 mothers) who live in Jakarta, Indonesia. The results, based on the use of the split sample technique and EFA and CFA tests, show that the MIPQ-Ind has two valid factors, as indicated by the index 2/df= 2.8, CFI = 0.9, GFI = 0.96, RMSEA = 0.06 and RMSR = 0.04. The internal structure validity is 0.913 for the ‘being in the moment with child’ (BMC) factor and 0.906 for the mindful discipline (MD) factor. The study shows that the MIPQ-Ind was able to measure mindful parenting in the population of parents with children aged 2-12 in Indonesia.